Manajemen Hubungan Masyarakat dengan Lembaga Pendidikan Islam - Louis, Muhammad Ariel Ramadhan; Khakim, M. Nurul; Untung, Slamet (TSAQOFAH, 2024)
This article aims to study the management of relations between society and Islamic educational institutions through literature study. Data was collected through literature search from books, articles, and journals related to the research topic. In this study, several factors that influence the management of relations between the community and Islamic educational institutions will be examined, such as openness and transparency in decision making, community participation in decision making, and the use of appropriate information and communication technology. The results showed that the management of relations between the community and Islamic educational institutions is very important in strengthening the mutually supportive relationship between the community and Islamic educational institutions. Community participation in decision-making can strengthen the relationship between the community and Islamic educational institutions. In addition, the use of information and communication technology can facilitate the process of relationship management between the community and Islamic educational institutions. This research also shows that the management of relations between the community and Islamic educational institutions can improve the quality of education organized by Islamic educational institutions. With community support and participation, Islamic educational institutions can be more responsive to the needs and expectations of the community in providing quality Islamic education.